Handbook of milk of non-bovine mammals - Haenlein, George F. W.; Park, Young W.; Wendorff, William L. (John Wiley & Sons, 2017)
"Featuring contributions by an international team of dairy and nutrition experts, this second edition of the popular Handbook of Milk of Non-Bovine Mammals provides comprehensive coverage of milk and dairy products derived from all non-bovine dairy species.